Real world outcomes using 20 mm balloon expandable SAPIEN 3/ultra valves compared to larger valves (23, 26, and 29 mm)–a propensity matched analysis - Eng, Marvin H.; Abbas, Amr E.; Hahn, Rebecca T.; Lee, James; Wang, Dee Dee; Eleid, Mackram F.; O'Neill, William W. (Catheterization and cardiovascular interventions, 2021)
Objective/Background Small balloon expandable valves have higher echocardiographic transvalvular gradients and rates of prosthesis‐patient mismatch (PPM) compared to larger valves. However, the impact of these echocardiographic findings on clinical outcomes is unknown. We sought to determine the clinical outcomes of 20 mm SAPIEN 3 (S3 BEV) compared to larger S3 BEV in relation to echocardiographic hemodynamics. Methods Using the STS/ACC transcatheter valve registry, we performed a propensity‐matched comparison of patients undergoing treatment of native aortic valve stenosis using transfemoral, balloon‐expandable implantation of 20 mm and ≥ 23 mm S3 BEVs. Baseline and procedure characteristics, echocardiographic variables and survival were analyzed. Multivariable logistic regression was used to identify predictors of 1‐year mortality. Results After propensity matching of the 20 mm and ≥ 23 mm SAPIEN 3 valves, 3,931 pairs with comparable baseline characteristics were identified. Small valves were associated with significantly higher echocardiographic gradients at discharge (15.7 ± 7.1 mmHg vs. 11.7 ± 5.5 mmHg, p < 0.0001) and severe PPM rates (21.5% vs. 9.7%, p < 0.0001). There was no significant difference in 1‐year all‐cause mortality (20 mm: 13.0% vs. ≥23 mm: 12.7%, p = 0.72) or other major adverse event rates and outcomes between the two cohorts. Based on a multivariable analysis, elevated discharge mean gradient (>20 mmHg), severe PPM and the use of 20 mm versus ≥23 mm were not independent predictors of 1‐year mortality. Conclusion SAPIEN 3 20 mm valves were associated with higher echocardiographic gradients, and severe PPM rates compared to larger valves but these factors were not associated with significant differences in 1‐year all‐cause mortality or rehospitalization.